Effizienzmessung als Bewertungskriterium für das Produktionskonzept In-Line mit Hilfe einer Data Envelopment Analysis - Jaroslaw Zaborek (MA Akademie Verlags- und Druck-Gesellschaft mbH, 2019)
– The transformation from traditional to integrated production systems reflects the evolvement of the industrial sector. The fourth industrial revolution, Industry 4.0 for short, is a technological evolutionary stage that emphasizes the importance of logistics in the overall production process. In addition to fulfilling the key requirements of customer orientation, satisfaction and flexibility, it is also vitally important, if not critical, to recognize the wider holistic factors that affect organizations' ability to operate, perform and deliver. To support the organizational holistic goals of cost savings and efficiency, and taking into consideration the transformation of the organization's principles with logistics and production, then this is facilitated through a process oriented adjustment strategy. Publication of this research paper marks the midpoint of the efficiency measurement as an evaluation criterion for the production concept In-Line with the help of a Data Envelopment Analysis. To measure efficiencies, various methods in literature help to assess the relationship between input and output factors. In addition to traditional comparisons of business key performance indicators, the Data Envelopment Analysis is a modern method based on production functions with multiple input and output factors. Although the efficiency analysis was originally developed for the public non-profit sector, various amendments of the DEA currently exist, in order to adapt it for use in semi-public and private sectors. This present research paper applies the DEA in the indus-try sector and examines the efficiency improvement of the In-Line concept. Besides the efficiency measurement, a comprehensive description of the In-Line concept is provided, which, under the aspect of Industry 4.0, can be regarded as a preliminary stage for the reorganization of business processes within logistics and production.
Keywords: 650